Geospace perturbations induced by the Earth: The state of the art and future trends. (2015) - De Santis, A.; De Franceschi, G.; Spogli, L.; Perrone, L.; Alfonsi, L.; Qamili, E.; Cianchini, G.; Di Giovambattista, R.; Salvi, S.; Filippi, E.; Pavón-Carrasco, F.J.; Monna, S.; et al.
Highlights: State of the art of the lithosphere–atmosphere–ionosphere coupling (LAIC) mechanisms. Earthquake-related case studies are shown together with unrelated cases. Models of LAIC are proposed with future trends of research. Abstract: A systematic multi-parameter and multi-platform approach to study the slow process of earthquake preparation is fundamental to gain some insights on this complex phenomenon. In particular, an important contribution is the integrated analysis between ground geophysical data and satellite data. In this paper we review some of the more recent results and suggest the next directions of this kind of research. Our intention is not to detect a particular precursor but to understand the physics underlying the various observations and to establish a reliable physical model of the preparation phase before an impending earthquake. In this way, future investigation will search for suitable fore-patterns, which the physical model of multi-layers coupling predicts and characterizes by quasi-synchronism in time and geo-consistency in space. We also present alternative explanations for some anomalies which are not actually related to earthquakes, rather to other natural or anthropic processes.